2020
DOI: 10.4178/epih.e2020051
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the number of Korean workers at high risk of COVID-19 infection

Abstract: We aimed to identify occupational groups at high-risk of coronavirus disease 2019 (COVID-19) infection in Korea, to estimate the number of such workers, and to examine the prevalence of protective resources by employment status. METHODS: Based on the sixth Standard Occupational Classification codes, 2015 census data were linked with data from the fifth Korean Working Conditions Survey, which measured how frequently workers directly come into contact with people other than fellow employees in the workplace. RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…In the context of the current COVID‐19 pandemic, our results also support existing evidence of nurses’ increased risk for exposure to infection with this virus globally (Gómez‐Ochoa et al, 2020; Nguyen et al, 2020). A study from Korea conducted among 30 professional groups including nurses ( N = 227,168) found that 44.2% of the sampled nurses reported high‐intensity exposure risk for infection with COVID‐19 (Lee & Kim, 2020). In a recent cross‐sectional study of nurses from Lebanon ( N = 311), 40% were classified at high risk for exposure to infection with the virus because they stated they rarely wore all PPE (especially goggles) when performing aerosol procedures with patients who had COVID‐19 (Saadeh, Sacre, Hallit, Farah, & Salameh, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the current COVID‐19 pandemic, our results also support existing evidence of nurses’ increased risk for exposure to infection with this virus globally (Gómez‐Ochoa et al, 2020; Nguyen et al, 2020). A study from Korea conducted among 30 professional groups including nurses ( N = 227,168) found that 44.2% of the sampled nurses reported high‐intensity exposure risk for infection with COVID‐19 (Lee & Kim, 2020). In a recent cross‐sectional study of nurses from Lebanon ( N = 311), 40% were classified at high risk for exposure to infection with the virus because they stated they rarely wore all PPE (especially goggles) when performing aerosol procedures with patients who had COVID‐19 (Saadeh, Sacre, Hallit, Farah, & Salameh, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As well, women are more prevalent among precariously employed workers. Precarious work engagement is linked with insecurity, low wages, lack of protection and insurance, and there is a dimension of gender inequity involved 31,32 . Unsurprisingly, one study showed that rates of SARS‐CoV‐2 infection were higher in workplaces with minimal enforcement of existing OHS standards 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Self-employed males were the main victim of COVID-19 comparing to the other professions of males [12,13]. The patients who recovered from COVID-19 may experience significant health effects in the future.…”
Section: Original Research Articlementioning
confidence: 99%